2020
DOI: 10.1002/ctm2.125
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of 5‐hydroxymethylcytosine in zw10 kinetochore protein as a promising biomarker for screening and diagnosis of early colorectal cancer

Abstract: Background As a new epigenetic biomarker, 5‐hydroxymethylcytosine (5hmC) is broadly involved in various diseases including cancers. However, the function and diagnostic performance of 5hmC in colorectal cancer (CRC) remain unclear. Results High‐throughput sequencing was used to profile 5hmC levels in adjacent normal colon, advanced adenomas, and CRC. The expression and 5hmC levels in zw10 kinetochore protein (ZW10) were significantly increased in the tissues and blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The 5-year survival rate of patients with CRC is 65% [ 32 ], but it is extremely low in advanced-stage CRC. Therefore, techniques that aid the implementation of treatment strategies for CRC are urgently required because they can improve patient survival [ 27 ]. Studies have reported that m6A modification plays a key role in CRC [ 4 , 5 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year survival rate of patients with CRC is 65% [ 32 ], but it is extremely low in advanced-stage CRC. Therefore, techniques that aid the implementation of treatment strategies for CRC are urgently required because they can improve patient survival [ 27 ]. Studies have reported that m6A modification plays a key role in CRC [ 4 , 5 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 293 T cells obtained from the American Type Culture Collection were cultured in Roswell Park Memorial Institute 1640 Medium with 10% FBS and penicillin/streptomycin (100 U/mL; Gibco, USA). METTL3 short hairpin RNA plasmid, CRB3 short hairpin RNA plasmid, or negative control (Genomeditech, China) were transfected using FuGene HD transfection reagent (E2311, Promega, USA) per the protocol used in a previous study [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Colon cancer is a very common cancer worldwide with high morbidity and mortality. Several kinetochore proteins have been identified as a novel regulator of carcinogenesis in colorectal cancer (Dang et al 2020;Bai et al Zhou et al 2020;Zhang et al 2021). In the present study, KNTC1, a key kinetochore component, was shown to be overexpressed in colon cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ve-year survival rate of CRC patients is 65% [32], the ve-year survival rate of patients with advanced-stage CRC is very low. Therefore, it is urgent to develop techniques for the treatment strategy of CRC, which would improve patient survival [27]. Studies have indicated that m6A modi cation plays a critical role in CRC [4,5,12,33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 293T cells obtained from ATCC were cultured in RPMI Medium 1640 with 10% fetal bovine serum and penicillin/streptomycin (100 U/mL) (Gibco, Carlsbad, USA). METTL3 short hairpin RNA plasmid (sh-METTL3), CRB3 short hairpin RNA plasmid (sh-CRB3) or negative control (sh-NC) (Genomeditech, China) were transfected using FuGene® HD transfection reagent (Promega, USA) according to a previous study [27].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%